DIFFICULTIES FACED BY STUDENTS OF ENGLISH EDUCATION DEPARTMENT OF UNIVERSITAS MUHAMMADIYAH YOGYAKARTA IN DOING GROUP DISCUSSION - Oryza Septaviana (FPB PBI 16 UMY 008, 2016)
Speaking skill is an important skill that students should master when they learn language. The ability of speaking can measure the success of learning language. To develop student speaking ability student need a technique to improve their speaking skill. One of technique to develop speaking skills is group discussion. Group discussion is one of the method has been implemented at English Education Department of UMY in language teaching and learning processes. Through discussion, the students practice to communicate with others in groups. Despite the benefit provided in group discussion, students commonly face some difficulties in doing group discussion. The purpose of this research is to find out the difficulties faced by students of EED of UMY in doing group discussion. This research used descriptive qualitative research design and used interview as the research instrument. The research was conducted in December 2015 at English Education Department of UMY. The participants of this research consisted of three female students of English Education Department of UMY batch 2014 who had experience in group discussion based on criteria. In analyzing the data, the researcher used open, axial and selective coding.